Formulasi Sediaan Tablet Hisap Ekstrak Kering Habbatus Sauda' (Nigella Sativa L.) dengan Kombinasi Sukrosa-Manitol sebagai Bahan Pengisi - Yulisa Raras Dewi; Andi Sri Suriati Amal; Lija Oktya Artanti (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2019)
Habbatus sauda' (Nigella sativa L) has been widely used by Indonesian people with capsule dosage form. In this study the researcher choose the form of suction tablets that aims to provide a form of treatment that can be given easily to children or elderly who are difficult to swallow the drug. This study aims to determine the physical characteristics of dry sucking tablets of habbatus sauda’ extracts with a combination of sucrose - mannitol as a filler material. Habbatus sauda' dried extract is made by water solvent and dried with freeze dryer. Habbatus sauda' dried extract tablet is made in 3 formulations with a combination of sucrose and mannitol namely FI (sucrose 1: manitol 5), FII (sucrose 1: manitol 6) and FIII (sucrose 1: manitol 7). The method of wet granulation is used in the production of dry sucking tablet of habbatus sauda’ dried extract. Granules tested include flow time test, silent angle, compressibility and moisture test. The habbatus sauda' dried extract suction tablets were tested for physical properties including weight uniformity, hardness, friability and tablet disolue time test. Data of granule test result and test of physical properties of tablet were compared with research, while granule flow time test and tablet hardness test were analyzed statistically using One Way ANOVA test with 95% confidence level. The results showed that there was an influence on the hardness and taste of suction tablets of habbatus sauda’ dried extract with a combination of sucrose-mannitol. From the result of the research, it can be concluded that the suction tablet of Habbatus sauda extract with sucrose concentration (1): mannitol (5) has good criteria as suction tablet with tablet hardness 8,57/kg, soluble time 13.27 / minute and 0,12% friability